Computer-Based Monitoring: Common Perceptions and Empirical Results* - George, Joey F. (MIS Quarterly, 1996)
Computer-based monitoring, the practice of collecting performance information on employees through the computers they use at work, continues to be a popular topic. How much is known about computer-based monitoring as it is practiced in the workplace? Unfortunately, very little, even though much has been written on the subject. This article reports on five case studies of organizations that employ computer-based monitoring to collect performance data on clerical workers. Although all five organizations utilize similar data collection methods and procedures, no two organizations use the data collected in the same ways to evaluate employee performance. Each site reports different levels of employee satisfaction with monitoring, different abilities of employees to balance demands for work quantity and quality, different levels of work-related illnesses, and different perceptions of supervision. Although these results do not appear surprising on the surface, much of the popular literature on computer-based monitoring stresses the negative effects of monitoring on workers, no matter how or where it is implemented. In this study, the simple presence of computer-based monitoring was not enough to explain differences between sites. Rather, other factors, such as which data were used for evaluation and outside economic pressures, helped to explain variations in monitoring and its effects across sites. Computer-based monitoring, like other information technologies, is a malleable technology.